HUBUNGAN KEPATUHAN PENGGUNAAN OBAT ANTIDIABETES DENGAN KEBERHASILAN TERAPI PADA PASIEN DIABETES MELITUS TIPE 2 RAWATJALAN DI POLIKLINIK PENYAKIT DALAM RSUD EMBUNG FATIMAH BATAM 2018 - Bratasena Silalahi; Nopri Esmeralda (Universitas Batam, 2019)
Diabetes mellitus (DM) is a disease, with the condition that glucose levels in the blood exceed normal limits. This is because the body cannot release or use insulin adequately. Insulin is a hormone released by the pancreas and is the main substance responsible for maintaining blood sugar levels in the body to remain in a balanced condition. Insulin functions as a tool that helps sugar move into cells so that it can produce energy or be stored as energy reserves. The purpose of this study was to determine the Correlation between the Compliance of the Use of Antidiabetic Drugs and the Success of Therapy in Type 2 Diabetes Mellitus Patients Outpatient in the Internal Medicine Polyclinic of Embung Fatimah Hospital in Batam 2018.Method: This type of research is an observational analytic cross-sectional study design. The number of samples is 40 people. Data collection techniques by giving questionnaires about compliance and medical record data of patients with type 2 diabetes mellitus. Univariate analysis is presented in the frequency distribution table and bivariate analysis using chi-square with the SPSS system.Results: The results of a study with a sample of 40 patients, showed more than half of patients (62.5%), had high adherence and more than half of patients (62.5%), successful treatment success. Chi-Square analysis results obtained p.value = 0.041 where p is smaller than the significance level (Î±) = 5% (0.05). Ho rejected, which means there is a significant relationship between compliance with the use of antidiabetic drugs with the success of therapy in patients with type 2 diabetes mellitus outpatient in the Internal Medicine Polyclinic at Embung Fatimah Hospital in Batam 2018.Conclusion: Based on this study it was concluded that there was a Compliance Relationship between the Use of Antidiabetic Drugs and the Success of Therapy in Type 2 Diabetes Mellitus Patients Outpatient in the Internal Medicine Polyclinic at Embung Fatimah Hospital in Batam 2018.